Design of device for gas shielding of joint during friction stir welding - I. K. Chernykh; E. V. Vasil`ev; E. I. Tkachenko; A. S. Lukin; D. A. Proshutinskiy; V. A. Valova; E. A. Savva (Омский научный вестник)
Due to its characteristics, titanium alloys are widely used in industries such as shipbuilding, aircraft manufacturing, rocket production, etc. Friction stir welding of titanium alloys is a perspective method for manufacturing parts in these industries. During the welding process, the temperature can reach more than 1200 С, while an active oxidation process occurs, which causes defects. To eliminate the formation of voids, it is necessary to use special devices for gas shielding. The existing devices for arc welding are not intended for friction stir welding. The aim of the study is to design device for supplying a shield gas during friction stir welding of titanium alloys, which will allow eliminating these defects. Friction stir welding of titanium alloys experiments are carried out using the developed device. As a result of the experiment, sound welds with no oxidation markers are produced.